2015
DOI: 10.1016/j.fertnstert.2015.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing pregnancy rates in intrauterine insemination are affected by late follicular-phase progesterone levels

Abstract: Significant differences in ongoing pregnancy rates when P levels were elevated on the day of hCG administration may help clinicians to counsel patients about the reduced success rates with IUI and manage the timing of insemination to optimize implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
(28 reference statements)
0
5
1
Order By: Relevance
“…The outcome of subsequent frozen embryo transer cycles were not negatively influenced by an elevated progesterone level at the moment of ovum retrieval during the index IVF treatment. Comparable effects have been observed in patients undergoing intrauterine insemination with mild ovarian stimulation (Requena et al, 2015). The incidence of premature progesterone elevation in our study is higher than that reported in intrauterine insemination with mild ovarian stimulation and IVF.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The outcome of subsequent frozen embryo transer cycles were not negatively influenced by an elevated progesterone level at the moment of ovum retrieval during the index IVF treatment. Comparable effects have been observed in patients undergoing intrauterine insemination with mild ovarian stimulation (Requena et al, 2015). The incidence of premature progesterone elevation in our study is higher than that reported in intrauterine insemination with mild ovarian stimulation and IVF.…”
Section: Discussioncontrasting
confidence: 63%
“…The incidence of premature progesterone elevation in our study is higher than that reported in intrauterine insemination with mild ovarian stimulation and IVF. This might be explained by the use of GnRH agonist and antagonist in IVF and the strict criterion of maximum dominant follicle size before administrating HCG in the study by Requena et al (2015). Moreover, this may reflect a local variation in progesterone assay performance, as this has been shown to be subject to local conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the influence of endometrial echogenicity on the success of IUI are scarce (32). However, a hyperechogenic endometrium is usually evidence of premature luteinization, which is currently associated with adverse reproductive outcomes after IUI (33). Other classical prognostic factors for the success of IUI, such as the duration of infertility (31,34), follicle number (30,31,34,35), E 2 at triggering (29,30,35), teratospermia (29,30,36), or NMSI (29,30,37), were not identified by our multivariate analysis, possibly because of a lack of power or appropriate controls for these parameters.…”
Section: Discussionmentioning
confidence: 99%
“…However, Kolibianakis et al [166] in a subsequent review demonstrated a significant adverse effect on PRs in GnRH antagonist cycles and the large 2013 systematic review and meta-analysis of more than 55,000 cycles from 63 publications, confirmed that progesterone rise on the day of hCG, decreases the probability of pregnancy in fresh IVF cycles [1]. Since then, the scientific dialog on the matter continues with various cut-offs, and even though there is some scars evidence of improved clinical results of preovulatory progesterone rise [7,12,167], or conclusions of no significant effect [122,124,126,[168][169][170], there are also clear reports of unfavorable results on CPR and LBR [22,24,52,96,99,112,116,117,129,131,137,145,151]. Venetis et al [133] demonstrated in a retrospective study that multivariable analysis taking into consideration multiple confounding factors revealed statistically significant decrease in LBR for cycles with progesterone rise on trigger day whereas bivariate analysis failed to do so in the same cohort.…”
Section: Success Ratesmentioning
confidence: 99%